Multiplexed action-outcome representation by striatal striosome-matrix compartments detected with a mouse cost-benefit foraging task - Bernard Bloem; Rafiq Huda; Ken-ichi Amemori; Alex S. Abate; Gayathri Krishna; Anna L. Wilson; Cody W. Carter; Mriganka Sur; Ann M. Graybiel (Nature Communications, 2022)
The role that the striatum plays in tracking the association between actions and combinations of rewarding and aversive outcomes remains unclear. Here, by using both calcium imaging in mice and reinforcement learning models, the authors find that individual striatal neurons can encode associations between actions and multiple, sometimes conflicting, outcomes.